Decentralized Autonomous Organization (DAO) – A Review - Mikhaylov, Dmitry; Shafeeg, Abdulla; Shazhaev, Ilman; Tularov, Arbi (The Indonesian Journal of Computer Science, 2023)
The idea of DAO development is a novel and radical solution to the constant centralization of power and financial capabilities of the world community. Unlike decentralized finance (DeFi) in general, which uses blockchain to replace trusted third parties in banking, lending, investing, and other financial transactions, DAOs use technology to transfer some or all decision-making power from organizations to individuals using a code for setting guidelines, namely how decisions are made and implemented. Investors place their digital assets in liquidity pools using code-driven smart contracts without the need for an intermediary to ensure that all parties meet their obligations. In exchange for their investment, investors receive a token that allows them to participate in the centralized management of the pool, including the ability to vote to choose which beneficiaries receive a portion of the income that becomes a donation and set parameters for smart contracts. And although this scheme, in addition to advantages, has disadvantages, the idea of DAO continues to develop. At the moment, this development is limited only to the digital environment. Yet, the perspective is impressive.